Efficient computation of the impedance matrix of magnetic field integral equation for polyhedral conductors - Shen, Zhongxiang (2015)
The vertical improper integral method is used to formulate a polyhedral magnetic field integral equation (MFIE), which can decrease the number of singular integrals compared with the traditional MFIE. Each element in the impedance matrix resulted from the equation’s moment method solution based on Rao-Wilton-Glisson (RWG) basis function is divided into two parts: the induced surface current part and the scattered field part. We obtain the analytical expressions of the induced surface current part through mathematical manipulations, and indicate that some of the integrals in the scattered field part are zero and the remaining non-zero integrals are non-singular. These results can greatly improve the efficiency of the numerical solution. Numerical results show that our new method is more accurate and efficient than the traditional method in computing the impedance matrices.